Toxicity of Cisplatin and Herbal Medicine Complexed with Bovine Serum Albumin (BSA) and Folic Acid Nanoparticles as Anticancer Candidates: Perbandingan Uji Toksisitas Obat Cisplatin dan Obat Herbal Kombinasi Nanopartikel Bovine Serum Albumin (BSA) dan Asam Folat Sebagai Kandidat Antikanker - Ersalina Nidianti; Rizka Amalia; Nisrina Salsabila Firdaus (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
The prevalence of cancer in Indonesia has increased by 8.8 percent in the last two years (2018 and 2020) in terms of adding new cases and mortality. Because of therefor cancer treatment becomes important in reducing the high number of additional new cases and mortality due to cancer patients. Intensive cancer treatment is by surgery, chemotherapy, radiotherapy and immunotherapy. Chemotherapy drugs used for cancer treatment include herbal plant-based cancer drugs (Cancer Fit) and cisplatin its buy from online shop. This study aims to compare the toxicity of herbal drugs (Cancer fit) with cisplatin, a combination of BSA nanoparticles and folic acid as anticancer candidates. The research method is through the synthesis of nanoparticles with the desolvation method, then characterization is carried out using XRD and FT-IR tests. After that proceed to the toxicity test with the BSLT method. The results obtained from XRD analysis on BSA and folic acid nanoparticles from cisplatin (As-NP-BSA-CP) showed a peak of 34.45 while BSA and folic acid nanoparticles from herbal medicine (As-NP-BSA-Oh) obtained a peak of 22.77. The purpose of XRD analysis was to determine the crystalline characteristics of the synthesized nanoparticles and to analyze the crystalline index. FT-IR analysis on (As-NP-BSA-CP) showed that there are functional groups O-H alcohol, C-H, C-C, NO2 that play a role in the synthesis of nanoparticles. Meanwhile, (As-NP-BSA-Oh) showed that the functional groups were C-H alkene, C-O alcohol, and C-N amine/amide. The toxicity level of As-NP-BSA-CP LC50 is 69.14 ppm while the toxicity level of As-NP-BSA-Oh LC50 is 44.14 ppm. Nanoparticles consisting of a combination of bovine serum albumin (BSA), folic acid and cisplatin drugs or herbal drugs can be used as candidates for anticancer drugs.